The Current State of Women's Co-operatives in Turkey - Duguid, Fiona; Durutaş, Gökçen; Wodzicki, Michael (World Bank, Washington, DC, 2017)
The report is structured in the following manner. The first chapter introduces the research objectives, methodology (literature reviews, survey, micronarratives and interviews), and limitations of the proposed methodology. The second chapter presents the global and Turkish context for women’s co-operatives. Chapter three profiles women’s co-operatives in Turkey, describing their origins, their membership, their business and their internal and external challenges. Chapter four discusses the impact of women’s co-operatives on their communities and their members. Chapter five and six present the supportive infrastructure for women’s co-operatives, namely the legal context for co-operatives in Turkey as it relates to Turkey’s co-operative strategy and international good practices; and the support programs that women’s co-operatives are asking for, and that are effective. The conclusion presents high level findings and links these findings to eleven recommendations that aim to strengthen women’s co-operatives in Turkey.